No-body homicide cases : a practical guide to investigating, prosecuting, and winning cases when the victim is missing - DiBiase, Thomas A. (Tad) (Boca Raton, FL : CRC Press, 2015)
'How do you prove someone is guilty of murder if there is no body? This practical guide for police and prosecutors provides an expansive look at both the history of no-body murder cases and the best methods to solve them and present the case in court. The author takes readers step by step through the first days of the homicide investigation though the end of the trial. The book is an essential resource for all investigators and a roadmap to a conviction for prosecutors.'--
'Introduction'How can you prosecute a murder without the body?' I cannot count the number of times I have been asked this question over the past ten years. My answer has always been the same:'Yes, it can be done and has been done, more times than you think.' If murder is the ultimate crime, then a'nobody' murder is the ultimate murder. In our nation's history there have been just under 400 no-body murder trials, that is, trials where the victim's body has never been found. Now, for the first time ever, this book will provide a practical guide for police and prosecutors facing the challenges in these cases. This book takes an expansive look at both the history of no-body murder cases and the best methods to solve and try them. I will take the reader step by step from the first days of a homicide investigation through the trial of a case involving the ultimate law enforcement challenge: proving someone guilty of murder when the best piece of evidence, the victim's body, is missing. In doing so, I examine the history of no-body cases and discuss why these cases are so difficult to investigate and prosecute. All of this is through the lens of my own experience investigating and trying a no-body case and having consulted on scores of no-body murder cases with police and prosecutors across the country. Exploring the history of confessions, jailhouse snitches, and CSI-style forensics,'No-Body' Homicide Cases: A Practical Guide to Investigating, Prosecuting, and Winning Cases When the Victim Is Missing offers an insider's view of modern homicide investigative techniques'--
The early investigative phase -- 2. The later investigative phase -- 3. Cold case -- 4. Trial -- 5. No-body murder case statistics -- 6. Personality of a murderer -- 7. Future.
Includes bibliographical references and index.
Keywords: Criminal Investigation -- United States; Criminal procedure -- United States; Murder -- Investigation -- United States; Trials (Murder) -- United States; Homicide investigation -- United States; Victims of crimes -- United States; Evidence, Criminal -- United States; Forensic sciences -- United States